Posturography in elderly people with vestibular disorder and falls - Macedo, Camila (2013)
Introduction: Static and dynamic posturography has been used to investigate the ability of older people with vestibular disorders to maintain balance under varying conflicting sensory conditions. The goal of testing is to quantify the velocity of oscillation and the center of pressure displacement in different conditions of visual, somatosensory and visual-vestibular conflicts, and the limit of stability. Objective: To analyze the literature of the quantitative assessment of postural stability and balance using static and dynamic computerized posturography in elderly patients with vestibular dysfunction. Methods: A research was performed in the databases LILACS, EMBASE, MEDLINE, Scielo, Cochrane, ISI Web of Knowledge and virtual libraries of theses and dissertations in publications of the last 20 years, using the keywords: “elderly”, “Postural Balance”, “Postural Control”, “Assessment”, “Falls”, “Posturography”, “Vestibular” and / or dizziness.” Results: There are several models of computerized posturography that measure the postural responses and the fall risk in older individuals, in different environmental sensory stimuli, including virtual reality technology. Elderly people with imbalance, dizziness, and/or a history of falls have worse performance than elderly with no complaints and no history of falls and younger subjects. Conclusion: The posturography is a valuable tool for quantitative analysis of postural control, and it allows identify the sensory conditions in which the elderly with vestibular disorders have major instability.